Nilai Erosi dengan Metode Rusle dari Pemanfaatan Citra Sentinel-2 di Wilayah Sungai Pasee Peusangan - Firman Hadi; Tito Eka Syafjanuar; Nasrul Arrahman; Ichwana Ramli (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2023)
Erosion of watercourses is a natural process related to the environment which has an adverse impact on the environment, through the organic, physical and chemical properties of the soil. This causes a decrease in soil productivity, pollutes rivers and fills water reservoirs. Erosion estimates were calculated using the Revised Universal Soil Loss Equation (RUSLE) with GIS to achieve the research objective. Calculations with the RUSLE method are carried out with the assumption that soil erosion occurs by 5 main factors, namely rain erosion (R), soil physical properties (K), land use status (C), erosion control area (P) and topography (LS). The RUSLE equation can also be used to calculate sediment. This study uses remote sensing imagery from Sentinel-2 MSI. In this research, to improve the geolocation accuracy of geometric correction and atmospheric correction using the Sentinel Application Platform, namely SNAP (Sentinel Application Platform). The results showed that most of the Pasee-Peusangan area was indicated as an area with low erosion, most of this area was in the north. While for the location to the south, there are different values indicating erosion, where the value is getting higher. Area Indications of moderate and high erosion in the Pasee-Peusangan is to the south, where this area has a mountainous topography with alluvial soil types, so the potential for erosion in this area is high. The highest erosion areas are scattered which are dominated in the several areas of the Peusangan highlands. Meanwhile for the Pasee, the highest erosion occurred in the transition and downstream (coastal) areas. Land management needs to be considered to be able to determine the causes of these differences.